International trade of cereals: The contribution of Romania - Irina Chiurciu; Elena Soare; Ion Certan; Aurelia Chereji; Dan Marius Voicilaş; Paula Stoicea (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
Benefiting from pedoclimatic conditions favorable to grain cultivation, Romania was an important player in international trades. In the context of the current geopolitical changes, the paper aims to identify the position occupied by Romania in the global trade of maize and wheat in the period 2017-2021. For this purpose, exports and imports of maize and wheat by quantity and value were analysed on the basis of statistical data available on speciality sites such as ITC. Thus, we note that in 2021, Romania ranked 5th in the ranking of corn exporters, in terms of quantity and 9th in terms of wheat exporters. The quantities and values recorded for the imports of maize and wheat indicated that Romania was not in the top positions in the world rankings, although there was an increasing trend in these indicators during the period under study.
Keywords: Q11; Q13; Q17; 330; cereals trade; maize; wheat; imports; exports; Romania